PENGARUH EXPERIENTIAL MARKETING TERHADAP REPEAT PURCHASE INTENTION PADA SEKTOR PARIWISATA BANDUNG (SURVEY PADA WISATAWAN YANG BERKUNJUNG KE KOTA BANDUNG) . - Ayulia Nirwani; Nur Azizah; Sophia Rahmi; Riffa Fauzany; Susanti Susanti (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Impact of Experiential Marketing experienced by tourists who visit Bandung which is based on the terms of Sense , Feel , Think , Act and Relate and their influences on Repeat Purchase Intention. This study was descriptive research. The results of this study suggest that repeat purchase intention can be enhanced by providing good experience in the form of sense, feel , think, act and relate. It was in order to create satisfaction on tourists who visit Bandung.